Kierkegaard´s search for an individual - Diatka, Cyril (Sincronía, 2026)
This article examines Søren Kierkegaard’s concept of the individual, emphasizing existence as a continuous task of self-creation. Through a critique of modern rationalism and the Hegelian system, the authors argue that, for Kierkegaard, the human being cannot be defined solely by abstract thinking, but rather by the dynamic unity of finitude and infinitude expressed in action, decision, and personal responsibility. The study explores the notion of the self’s relationship to itself and to God, highlighting that authentic existence emerges when the individual consciously assumes this relationship. The article also analyzes the three stages of existence—the aesthetic, ethical, and religious—as different modes of self-realization grounded in existential decisions rather than linear development. The aesthetic stage is characterized by immediacy and pleasure, the ethical by responsibility and conscious choice, and the religious by the leap of faith and an absolute relationship with the absolute. The article concludes that Kierkegaard’s philosophy remains highly relevant in the face of modern and postmodern challenges by reaffirming the centrality of the individual, concrete existence, and personal responsibility against abstract systems.